Trade implies law the power of the weak - Anderson, James E. 1943-; Young, Leslie (National Bureau of Economic Research, 2000)
Without the rule of law, traders who incur trading costs can be held up by counter-parties who are stronger in anarchic bargaining. The favourable terms which the latter extract can overcrowd that side of the market, dissipating the benefits. We establish plausible necessary and sufficient conditions for a move from anarchy toward the rule of law to benefit all traders. The rule of law might be delayed, not only by the difficulties of setting up legal institutions, but by monopolistic traders that have meantime emerged to address the inefficiencies of anarchic trade. These monopolistic traders must also guarantee atomistic traders against holdup.
Keywords: Ökonometrisches Modell; Commercial treaties -- Econometric models; Foreign trade regulation -- Econometric models; International trade -- Econometric models; Rule of law -- Economic aspects -- Econometric models